(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2006)
Magnesium oxide-based minerals such as serpentine and olivine may be used for long-term storage of CO2, from combustion of fossil fuels or industrial processes such as steel works, in the form of magnesium carbonate. Large resources of suitable minerals appear to exist in Finland and at many other locations worldwide. The efficiency of the mineral carbonation process can be evaluated using exergy analysis, which will allow for comparing different mineral deposits that are characterised by different composition and quality. Other factors that play a role are the temperature and pressure, the presence of other gases besides CO2 and the degree of magnesium carbonation that is reached. Important for the analysis is the calculation of the standard chemical exergy of the chemical species involved.